Making the Web Faster with HTTP 2.0. - GRIGORIK, ILYA (Communications of the ACM, 2013)
The article discusses various aspects of HyperText Transfer Protocol (HTTP) 2.0, a new version of the Internet application protocol as of December 2013. Background is presented on the history of the original HTTP including its success and the issues that have emerged recently. It highlights the performance challenges that come with modern Internet applications including the increase in online traffic caused mainly by mobile networks. The performance limitations of HTTP 1.1 are also highlighted including the failure of its request pipelining feature due to lack of support.